\(2sin^2x+3cos^2x=\dfrac{9}{4}\)...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

17 tháng 11 2022

a: tan x=cot x

=>tan x=tan(pi/2-x)

=>x=pi/2-x+kpi

=>2x=pi/2+kpi

=>x=pi/4+kpi/2

=>x=pi/4

b: =>\(2\cdot\dfrac{1-cos2x}{2}+3\cdot\dfrac{1+cos2x}{2}=\dfrac{9}{4}\)

\(\Leftrightarrow1-cos2x+\dfrac{3}{2}+\dfrac{3}{2}cos2x=\dfrac{9}{4}\)

=>1/2cos2x=-1/4

=>cos2x=-1/2

=>2x=2/3pi+k2pi hoặc 2x=-2/3pi+k2pi

=>x=1/3pi+k2pi hoặc x=-1/3pi+k2pi

=>x=pi/3

12 tháng 10 2019

a) Ta có: \(\sin^2\alpha+\cos^2\alpha=1\)

\(\sin\alpha=\cos\alpha\)\(2\sin^2\alpha=1\)\(\sin^2\alpha=\frac{1}{2}\)

\(\sin\alpha=\frac{1}{\sqrt{2}}\)\(\alpha=45\)độ

b) \(2\sin^2\alpha+3\cos^2\alpha=\frac{9}{4}\)

\(2\left(\sin^2\alpha+\cos^2\alpha\right)+\cos^2\alpha=\frac{9}{4}\)\(\cos^2\alpha=\frac{1}{4}\)

\(\cos\alpha=\frac{1}{2}\)\(\alpha=30\) dộ

13 tháng 10 2019

Cảm ơn cảm ơn

28 tháng 7 2018

ta có : \(cos^2x-2sin^2x=\dfrac{1}{4}\Leftrightarrow1-3sin^2x=\dfrac{1}{4}\)

\(\Leftrightarrow sin^2x=\dfrac{1}{4}\Leftrightarrow sinx=\pm\dfrac{1}{2}\) \(\Rightarrow x=30^o\overset{.}{,}x=330^o\)

ta có : \(cos^2x-2sin^2x=\dfrac{1}{4}\Leftrightarrow3cos^2x-2=\dfrac{1}{4}\)

\(\Leftrightarrow cos^2x=\dfrac{3}{4}\Leftrightarrow cosx=\pm\dfrac{\sqrt{3}}{2}\) \(\Rightarrow x=30^o\overset{.}{,}x=150^o\)

vậy\(x=30^o\overset{.}{,}x=330^o\overset{.}{,}x=150\)

24 tháng 4 2017

ĐS: a) x20x≈20∘;

b) x57x≈57∘;

c) x57x≈57∘;

d) x18x≈18∘.

24 tháng 4 2017

a) x20x≈20∘;

b) x57x≈57∘;

c) x57x≈57∘;

d) x18x≈18∘.

24 tháng 6 2018

\(\left(\dfrac{x-4}{2x-4}+\dfrac{2}{x^2-2x}\right):\dfrac{x-2}{x+1}\)

\(=\left(\dfrac{x-4}{2\left(x-2\right)}+\dfrac{2}{x\left(x-2\right)}\right).\dfrac{x+1}{x-2}\)

\(=\dfrac{x\left(x-4\right)+4}{2x\left(x-2\right)}.\dfrac{x+1}{x-2}\)

\(=\dfrac{x^2-4x+4}{2x\left(x-2\right)}.\dfrac{x+1}{x-2}\)

\(=\dfrac{\left(x-2\right)^2\left(x+1\right)}{2x\left(x-2\right)\left(x-2\right)}\)

\(=\dfrac{x+1}{2x}\)

25 tháng 6 2018

Mình làm nốt bài 2 nhé :

\(\dfrac{a}{b+c}+\dfrac{b}{c+a}+\dfrac{c}{a+b}=1\)

\(\left(a+b+c\right)\left(\dfrac{a}{b+c}+\dfrac{b}{c+a}+\dfrac{c}{a+b}\right)=a+b+c\)

\(\dfrac{a^2+a\left(b+c\right)}{b+c}+\dfrac{b^2+b\left(c+a\right)}{c+a}+\dfrac{c^2+c\left(a+b\right)}{a+b}=a+b+c\)

\(\dfrac{a^2}{b+c}+a+\dfrac{b^2}{c+a}+b+\dfrac{c^2}{a+b}+c=a+b+c\)

\(\dfrac{a^2}{b+c}+\dfrac{b^2}{c+a}+\dfrac{c^2}{a+b}=0\)


a: \(0< \sin x< 1\)

nên \(\sin x-1< 0\)

b: \(0< \cos x< 1\)

nên \(1-\cos x>0\)